2017
DOI: 10.1016/j.ijsu.2017.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences pre-, intra-, and postcholecystectomy: A retrospective cohort study of 6,868 patients

Abstract: Older patients have distinct pre-, intra-, and postoperative characteristics. Their care is more imaging- and cost-intensive. CCY in this population is associated with higher risks, likely due to a combination of comorbidities and age-related worsened physiological status. Pathologic findings are significantly different relative to younger patients. While removing the effect of age, preoperative creatinine levels, blood loss, and history of previous operation predict postoperative complications. Quantifying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although LC is considered safe, the rate of morbidity and mortality may be significant in some groups of patients, such as elderly, morbidly obese and immunosuppressed patients 9,17 . LC perioperative morbidity and mortality are usually considered higher in the elderly due to low physiologic reserve and associated diseases [18][19][20][21] . and gallbladder carcinoma [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LC is considered safe, the rate of morbidity and mortality may be significant in some groups of patients, such as elderly, morbidly obese and immunosuppressed patients 9,17 . LC perioperative morbidity and mortality are usually considered higher in the elderly due to low physiologic reserve and associated diseases [18][19][20][21] . and gallbladder carcinoma [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…The chronological age used to define an elderly or old person ranges in the medical literature from 60 to 80 years 7,9,18,25 . We used the World Health Our findings are also in agreement with previous studies, which have shown that the rate of males, jaundice, prior abdominal operations, and ASA scores II, III, and IV were higher in the elderly than in the younger group 1,8,11,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…While some authors have reported age-related pre-, intra- and postcholecystectomy differences, highlighting the fact that the elderly people were predisposed to develop various complications, including PCS, other researchers did not find any clear evidence supporting the idea of high risk for PCS in older age. 54 , 55 The results of the present study have shown that PCS (+) group displayed significantly older age by comparison to those without PCS.…”
Section: Discussionmentioning
confidence: 46%
“…Cholesterol polyps (cholesterolosis) are the most common, benign non-neoplastic, non-inflammatory lesions of the gallbladder 6. The prevalence of cholesterolosis varies from 9% to 26% and cholesterolosis is more likely to be present in young adults 7 8. An association between cholesterolosis and high BMI is found 9.…”
Section: Discussionmentioning
confidence: 99%